Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Pembuatan Sabun Cuci Piring - Rahmi Rismayani Deri; Noneng Nurhayani; Syafaruddin Mahaputra; Ega Triyandi (LPPM UNINUS, 2020)
Babakan Sari Village based on having the most dense population the district, the population of female sex is greater than male sex, the majority of the population is engaged in trading and private sector employees. And based on the identification results of the Babakan Sari Village, most of them are housewives, where some claim the high level of daily expenses so that they cannot meet their daily needs. The purpose of this training is to empower housewives to increase their knowledge, competence, save spending on buying dish soap and can be used as a new livelihood when traded. The method used in the training of making dishwashing liquid soap in the form of exposure, simulation, demonstration and practice is carried out classically. Most of the participants felt that they had mastered the material that was given, mastered the practice of making dish soap in the village of Babakan Sari Bandung. Participants also considered that the trainer had a very good ability to provide material and train participants.